1998
DOI: 10.3758/bf03208848
|View full text |Cite
|
Sign up to set email alerts
|

Perception of pictorial depth cues by pigeons

Abstract: Pigeons were trained to discriminate pictures of intact objects from pictures of objects in which both depth from shading and depth from perspective cues were manipulated. Depth from shading was manipulated either by scrambling or by removing three-dimensional shading cues. Depth from perspective was manipulated either by presenting pictures of objects with a two-dimensional outline (l.e., a square) or with a three-dimensional outline (Le., a cube). Transfer tests with novel images suggest that pigeons perceiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 24 publications
(21 reference statements)
2
22
0
Order By: Relevance
“…They concluded that the ability of these avian species to recognize equivalence between pictures and real objects is severely limited when a behavioral task requires a relatively precise correspondence. Although there is evidence that pigeons transfer discrimination from objects to pictures (e.g., Cabe, 1976;Delius, 1992;Watanabe, 1993) and that pigeons may have the ability to use 2-D cues to perceive three dimensionality (Cook & Katz, 1999;Reid & Spetch, 1998;Spetch, Kelly, & Lechelt, 1998), little is known about avian recognition of 2-D images of complex natural objects. In Experiments 2 and 3, we explored this issue.…”
Section: Resultsmentioning
confidence: 98%
“…They concluded that the ability of these avian species to recognize equivalence between pictures and real objects is severely limited when a behavioral task requires a relatively precise correspondence. Although there is evidence that pigeons transfer discrimination from objects to pictures (e.g., Cabe, 1976;Delius, 1992;Watanabe, 1993) and that pigeons may have the ability to use 2-D cues to perceive three dimensionality (Cook & Katz, 1999;Reid & Spetch, 1998;Spetch, Kelly, & Lechelt, 1998), little is known about avian recognition of 2-D images of complex natural objects. In Experiments 2 and 3, we explored this issue.…”
Section: Resultsmentioning
confidence: 98%
“…Because similar tests have not done with the pigeons, it is difficult to know if the starlings are similar or differ in this aspect. In general, experiments looking at the effects of shadows with pigeons have generally not found a strong contribution of this factor to shape perception (Cavoto & Cook, 2006; Reid & Spetch, 1998). Previous research in humans has shown that cast shadows are more important in identifying global spatial relationships of objects in a scene than making any contribution to shape perception (Mamassian, Knill, & Kersten, 1998), although that investigation focused on the perception of extrinsic cast shadows, instead of intrinsic cast shadows as tested here.…”
Section: Discussionmentioning
confidence: 95%
“…While prior studies with birds have employed a variety of methods, making generalization difficult, they suggest that some of these lighting cues are used in both natural and laboratory settings (Cavoto & Cook, 2006; Hershberger, 1970; Hess, 1950; Reid & Spetch, 1998; Rowland, Cuthill, Harvey, Speed, & Ruxton, 2008; Young, Peissig, Wasserman, & Biederman, 2001). …”
mentioning
confidence: 99%
“…The most surprising result in our study was the large decrement in accuracy that was caused by changes in the direction of lighting (in our personal observations of the program as it was presenting the stimuli, we usually failed to notice that the light-changed stimuli were not the original training stimuli). In another study exemplifying sensitivity to internal surface features, Reid and Spetch (1998) tested the pigeon's ability to use surface features to discriminate which of two two-dimensional images was a valid representation of a three-dimensional object. They found that pigeons can use internal surface variations in a way that is consistent with the classification of images as valid representations of three-dimensional objects, thus evidencing sensitivity to the configuration of these internal surface features.…”
Section: Discussionmentioning
confidence: 99%